THE CONCEPT OF FINANCIAL STABILITY OF INSURANCE COMPANIES AND ITS THEORETICAL BASIS (American Journal of Business Management, Economics and Banking, 2024)
This article discusses the issues of improving the practice of ensuring the financial stability of insurance companies, and discusses the scientific and theoretical views of foreign and domestic economists on the development of the insurance market and ensuring the financial stability of insurance companies. It also covers the classification of financial stability of insurance companies and factors affecting the financial stability of insurance companies. In addition, practical conclusions and theoretical recommendations are formulated to improve the practice of ensuring the financial stability of insurance companies.